Influence of Thermal Aging on the Combustion Characteristics of Cables in Nuclear Power Plants - Min Ho Kim; Hyun Jeong Seo; Sang Kyu Lee; Min Chul Lee (Energies, 2021)
In this study, the combustion characteristics and emission of toxic gases of a non-class 1E cable in a nuclear power plant were investigated with respect to the aging period. A thermal accelerated aging method was applied using the Arrhenius equation with the activation energy of the cables and the aging periods of the cables set to zero, 10, 20, 30 and 40 years old by considering the lifetime of a nuclear power plant. According to ISO 5660-1 and ISO 19702, the cone calorimeter Fourier transform infrared spectroscopy test was performed to analyze the combustion characteristics and emission toxicity. In addition, scanning electron microscopy and an energy dispersive X-ray spectrometer were used to examine the change in the surface of the sheath and insulation of the cables according to the aging periods. To compare quantitative fire risks at an early period, the fire performance index (FPI) and fire growth index (FGI) are derived from the test results of the ignition time, peak heat release rate (PHRR) and time to PHRR (tPHRR). When comparing FPI and FGI, the fire risks decreased as the aging period increased, which means that early fire risks may be alleviated through the devolatilization of both the sheath and insulation of the cables. However, when comparing heat release and mass loss, which represent the fire risk at the mid and late period, fire intensity and severity increased with the aging period. The emission of toxic gases coincided with the results obtained from the heat release rate, which confirms that the toxicity of non-aged cables is higher than that of aged cables. From the results, it can be concluded that the aging period significantly affects both the combustion characteristics and toxicity of the emission gas. Therefore, cable degradation with aging should be considered when setting up reinforced safety codes and standards for cables and planning proper operation procedures for nuclear power plants.